Penerapan Metode Card Sort Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PKn Kelas IV MIN 2 Pandeglang - Dina Khoirunnisa; Nandang Kosim; Agus Hidayatullah (Universitas Garut, 2025)
This study aims to describe the application of the card sort method in improving student learning outcomes in Civics Education (PKn) on the subject of mutual cooperation in class IV C MIN 2 Pandeglang. This study uses a Classroom Action Research (CAR) approach conducted in two cycles. The research subjects were 30 students in class IV C MIN 2 Pandeglang. Data collection techniques included observation, learning outcome tests, and documentation. Data analysis was conducted using descriptive qualitative and quantitative methods. The results showed an increase in student learning outcomes after the application of the card sort method. At the beginning of the study, only 12 students or 40% achieved the Minimum Completion Criteria (KKM). After the intervention in cycle I, the number of students who achieved mastery increased to 21 students or about 70%. In cycle II, learning mastery increased significantly to 27 students or 90%. In addition to improving learning outcomes, the card sort method was also able to increase student activity, cooperation, and understanding of the learning material. Keywords: Card Sorting Method, Learning Outcomes, Civics